Aktivitas fisik dengan penyakit jantung koroner di Indonesia - Diyan Yunanto Setyaji; Yayi Suryo Prabandari; I Made Alit Gunawan (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Coronary heart disease (CHD) is responsible for a substantial amount of early deaths, reduced quality of life and significant costs to the health and social care system. More than 3/4 CHD cases can prevented by lifestyle changes and focus on earlier risk factors management. Physical activity become a reference for the most important of primary and secondary prevention.Objective: To determine the relationship between physical activity and coronary heart disease in Indonesia.Method: This study used a cross-sectional design. Coronary heart disease’s history, physical activity, age, sex, economic status and consumption of fatty food were obtained from Basic Health Research (Riskesdas) 2013. Riskesdas 2013 used multistage cluster sampling. Subject in this study was 374.506 women and 347.823 men above 15 years old in Indonesia who answered the coronary heart disease questions which was selected purposively. Data was analyzed by using descriptive analysis, Chi-Square and multiple logistic regression.Results: Those who did not perform vigorous-intensity physical activity or who only did it less than 80 minutes per week had a higher prevalence of CHD than those who were more active [2.63 (2.44-2.86); p=0.00].Conclusion: Physical activity had a significant association with CHD events in people above 15 years old in Indonesia.